Optimization Increases Customer Satisfaction Through Mudharabah Financing Products and Brand Image - Adetia Azmi Tanjung; Hajar Affiah (Syntax Corporation Indonesia, 2022)
The purpose of this study is to analyze the effect of mudharabah financing and brand image partially and simultaneously on customer satisfaction at Commercial Islamic Banks. This type of research is classified as associative. The population and sample in this study were 92 respondents with a sampling technique using an accidental sampling approach. The results showed that both partially and simultaneously mudharabah and brand image had a positive and significant effect on customer satisfaction at Commercial Islamic Banks. Mudharabah financing variable has a greater influence than brand image in influencing customer satisfaction at Commercial Islamic Banks.